Aspects related to the pregnancy and post-partition of women undergoing bariatric surgery - Silva, Luana Fernandes e (2021)
Objective: To analyze the sociodemographic, gynecological-obstetric, clinical and behavioral aspects related to pregnancy and postpartum women submitted to bariatric surgery. Method: This is a prospective cohort, with 33 women undergoing bariatric surgery, in a private hospital in Minas Gerais. Data collection took place through a semi-structured questionnaire, applied through telephone calls. The analyzes were performed using the Stata software, version 14.0. Results: The gynecological-obstetric profile showed that 78.79% of women showed improvement in sexual performance after bariatric surgery. Of these, 51.52% had a cesarean section as their route of birth. 96.97% of women did not report complications after pregnancy, 76% were able to breastfeed and 69.57% had no complications during breastfeeding. 81.25% did not report any health complications of the baby. The clinical profile showed that 63.64% were not followed up by a nutritionist after the surgery and 78.79% were not followed up by a psychologist or psychiatrist. 96.97% were not diagnosed with Systemic Arterial Hypertension after bariatric surgery and 100% were not diagnosed with Diabetes Mellitus after the surgical procedure. Finally, the behavioral profile showed that 78.79% of women did not practice physical activity in the last 3 months, 66.67% did not consume alcohol and 87.88% were not smokers. Conclusion: The bariatric surgery procedure is related to positive outcomes, therefore, the maintenance of these factors is related to the way of facing new life habits and multiprofessional monitoring. Despite the proven benefits of the surgical procedure, it can lead to maternal and fetal clinical and nutritional complications.